2019
DOI: 10.25165/j.ijabe.20191203.4468
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water stress at different growth stages on comprehensive fruit quality and yield in different bunches of tomatoes in greenhouses

Abstract: The aim of this study was to investigate the effects of tomato quality and yield between different bunches and the differences between the two comprehensive evaluation methods on tomato quality ranking under water stress. Two degrees of water stress including mild water stress (W1) and moderate water stress (W2), and three growth stages that water stress applied including seedling stage (S1), flowering stage (S2) and fruit expanding stage (S3) were tested in this study. The yield and quality of different bunch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The reasonable combination of N, P and K can effectively improve the yield and fruit quality of trees. Studies have shown that these nutrients and their interactions have a remarkable influence on citrus yield, quality and soil residual available nutrients [3]; The combined application of N, P and K can increase the yield and improve fruit quality of kiwifruit [28]. The…”
Section: Discussionmentioning
confidence: 99%
“…The reasonable combination of N, P and K can effectively improve the yield and fruit quality of trees. Studies have shown that these nutrients and their interactions have a remarkable influence on citrus yield, quality and soil residual available nutrients [3]; The combined application of N, P and K can increase the yield and improve fruit quality of kiwifruit [28]. The…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of different drought-resistant cultivars to drought stress is also one of the key factors affecting soybean yield and quality (Hao et al 2010). Wang et al (2022) conducted a study on soybean drought resistance screening and found that drought-resistant cultivars can accumulate more soluble sugars under drought to reduce cell permeability, maintain metabolic activity and improve drought resistance.…”
Section: Resultsmentioning
confidence: 99%
“…2022) and the rank sum ratio model (Hao et al. 2019), were used to comprehensively analyse these indicators.…”
Section: Methodsmentioning
confidence: 99%
“…The 100-grain weight (HW), grains per ear (GN), grain moisture content (MCG), fresh ear yield (FY) and fresh ear yield with husk (HFY), the ear total nitrogen (TN), grains total starch (St), soluble sugar (SS), lysine (Lys) and total protein (TP) of the eight treatments were collected in the two waxy maize growing seasons. Four evaluation models, that is, the entropy weight method (Liang et al 2022), the TOPSIS method (Shih, Shyur, and Lee 2007), the principal component analysis method (Huang, Zhang, et al 2022) and the rank sum ratio model (Hao et al 2019), were used to comprehensively analyse these indicators.…”
Section: Comprehensive Evaluationmentioning
confidence: 99%